The The Effectiviness Of Implementing Fingerprint Attendance In Improving Employee Work Discipline At The Gorontalo City Regional Secrerariat Office - supangkat, Nur Rahma Ningsih; Abdussamad, Juriko; Tui, Fenti Prihatini Dance (PROVIDER JURNAL ILMU PEMERINTAHAN, 2025)
This research aims to find out how effective the application of fingerprint attendance is in improving employee work discipline at the Gorontalo City Regional Secretariat Office.  Judging from several indicators such as (1) Target Achievement (2) Adaptability (3) Job Satisfaction (4) Responsibility. The type of research used is the qualitative research method, which is a form of research that aims to provide a general overview in the form of data collected from the field for the purpose of descriptive research. The data collection techniques used were interviews, observation and documentation directly in the field. The results of this research show that achieving targets when implementing finger print attendance can be said to be effective, this can be seen in employees from the increased level of attendance compared to still using manual attendance, and it also makes it easier for employees to carry out the attendance process. In addition to the adaptability of Gorontalo City regional secretariat office employees, employees already understand the procedures and use of attendance fingerprints and are able to adapt from manual attendance to fingerprint attendance. Then job satisfaction for Gorontalo City regional secretariat employees has provided comfort in terms of usefulness and increased employee motivation with additional incentives for employees.  Meanwhile, it can be said that the responsibilities of the Gorontalo City regional secretariat employees are still not optimal because there are still some employees who only take attendance but after that are not in the room without leaving clear information. Penelitian ini bertujuan untuk mengetahui bagaimana Efektivitas Penerapan Absensi Finger Print Dalam Meningkatkkan Disiplin Kerja Pegawai Pada Kantor Sekretariat Daerah Kota Gorontalo.  Dilihat dari beberapa indikator seperti (1) Pencapaian Target (2) Kemampuan Adaptasi (3) Kepuasan Kerja (4) Tanggung Jawab. Jenis penelitian yang digunakan yaitu metode penelitian kualitatif yaitu suatu bentuk penelitian yang bertujuan untuk memberikan gambaran umum berupa data yang dikumpulkan dari lapangan secara objektif dengan jenis penelitian deskriptif. Teknik pengumpulan data yang digunakan yaitu wawancara, observasi dan dokumentasi secara langsung dilapangan. Hasil penelitian ini menunjukan bahwa untuk pencapaian target pada saat penerapan absensi finger print ini sudah bisa dikatakan efektif, hal ini dapat dilihat pada pegawai dari tingkat kehadirannya yang meningkat dibandingkan masih menggunakan absensi manual selain itu juga memudahkan pegawai dalam melakukan proses absensi. Selanjutnya kemampuan adaptasi pegawai kantor sekretariat daerah kota gorontalo, pegawai sudah mengerti tata cara dan penggunaan absensi finger print serta mampu menyesuaikan diri dari absensi manual ke absensi finger print. Kemudian kepuasan kerja bagi pegawai sekretariat daerah kota gorontalo sudah memberikan kenyamanan dalam hal penggunaannya dan meningkatnya motivasi pegawai dengan adanya penambahan insentif kepada pegawai. Sedangkan tanggung jawab dari para pegawai sekretariat daerah kota gorontalo bisa dikatakan belum maksimal karena masih ada beberapa pegawai yang hanya melakukan absensi tetapi setelah itu tidak berada di dalam ruangan tanpa meninggalkan keterangan yang jelas.